THE INCIDENCE AND PREVALENCE OF DENTAL-PERIODONTAL PATHOLOGY AND EDENTATION IN MOLDAVIA - Norina Consuela Forna (Romanian Dental Association for Education, 2014)
The proper rehabilitation of the partially extended edentulous patient should lead to a state of balance between the elements of the stomatognathic system and the therapeutic option selected, for a period of time as long as possible. Aim of the study Through the present study we aim at outlining the importance of a general biological perspective on the entire organism, the interrelation between the organism and the stomatognathic system and the necessity of a complex rehabilitation in view of reaching positive and long lasting balance. Material and methods 4503 individuals from the urban and rural areas of Iasi were evaluated. The modality of evaluation was the correlation of the clinical exam with the data from the specially drafted questionnaire in view of determining the behavioral pattern regarding the oral health, a sine-qua-non condition for a clear reflection of the oral pathology that is specific to the environment of origin. Results With regard to the general condition of the investigated subjects, one can notice a prevalence of a poor general condition in the urban area in proportion of 72.1% as compared to 27.9% in the rural area.The first position in the sphere of general affections is taken by cardiovascular diseases, in both environments, the higher percentage belonging to the urban area. In the urban area, the oral pathology has a prevalence plus in 2013 for the odontal lesions, unlike the previous years, this first pathology being followed by the periodontal lesions with the same ascending dynamic for 2013. Conclusions We need to underline the fact the we need continuity with regard to the prophylaxis of the general and or al condition in Iasi county, both in the rural and the urban environment, the necessity for sanitary education being an essential condition for the increase of the degree of population's health.